2021
DOI: 10.1101/2021.12.27.474273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structures of the Omicron spike trimer with ACE2 and an anti-Omicron antibody: mechanisms for the high infectivity, immune evasion and antibody drug discovery

Abstract: The Omicron variant of SARS-CoV-2 has rapidly become the dominant infective strain and the focus efforts against the ongoing COVID-19 pandemic. Here we report an extensive set of structures of the Omicron spike trimer by its own or in complex with ACE2 and an anti-Omicron antibody. These structures reveal that most Omicron mutations are located on the surface of the spike protein, which confer stronger ACE2 binding by nearly 10 folds but become inactive epitopes resistant to many therapeutic antibodies. Import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
(12 reference statements)
3
18
0
Order By: Relevance
“…The introduction of mutations in the spike region changes the conformation as shown previously with D614G, Alpha and Delta variants, thus modulating the binding to hACE2 receptor which in turns determine virus entry and immune escape to vaccines [43][44][45] Here, we have shown that variants including Omicron spike and synthetic spike mutants expressed on surface binds to soluble-hACE2 at a higher fold as compared to ancestral spike protein (Fig1b), which corroborates with other reported studies 46,47 . Furthermore, we have found that all the variants, including Omicron pseudoviruses showed signi cant increase in infectivity titer in 293T-hACE2 cells (Fig2a); however as compared to Delta variant, the infectivity titer did not increase in TMPRSS2 expressed 293T cell line.…”
Section: Discussionsupporting
confidence: 92%
“…The introduction of mutations in the spike region changes the conformation as shown previously with D614G, Alpha and Delta variants, thus modulating the binding to hACE2 receptor which in turns determine virus entry and immune escape to vaccines [43][44][45] Here, we have shown that variants including Omicron spike and synthetic spike mutants expressed on surface binds to soluble-hACE2 at a higher fold as compared to ancestral spike protein (Fig1b), which corroborates with other reported studies 46,47 . Furthermore, we have found that all the variants, including Omicron pseudoviruses showed signi cant increase in infectivity titer in 293T-hACE2 cells (Fig2a); however as compared to Delta variant, the infectivity titer did not increase in TMPRSS2 expressed 293T cell line.…”
Section: Discussionsupporting
confidence: 92%
“…However, the recently released two RBD-down one RBD-up model (PDB: 7TB4) 34 offers additional evidence, which we incorporate into our analysis in addition to our fixed model. Further early evidence of decreased three RBD-down conformational stability is provided by thermal shift assay and hydrogen deuterium exchange mass spectrometry in Yin et al 39 Together, these data and the data on RaTG13 versus SARS-CoV-2 from Wrobel et al 31 support our hypothesis and warrant further investigation of Omicron mutations at the RBD down -RBD down interface.…”
Section: Limitations Of the Studysupporting
confidence: 70%
“…These predictions can be validated experimentally and explained in more mechanistic detail once an Omicron spike structure in the three RBD-down conformation is solved. Indeed, early work by Yin et al to solve a three RBD-down structure with accompanying thermal shift and hydrogen-deuterium exchange mass spectrometry experiments observed significant shifts for Omicron as compared with wild-type (WT) spike, 39 suggestive of decreased three RBD-down state stability.…”
Section: Enhanced Ace-2 Bindingmentioning
confidence: 99%
“…The conformational and electrostatic changes induced by RBD mutations help to understand the enhanced ACE2-binding affinity by the Omicron spike (Lan et al, 2022;Mannar et al, 2021;Yin et 2021). The electrostatic analysis revealed the RBM to contain more positive charges than the Wuhan strain (Figure S4E).…”
Section: Discussionmentioning
confidence: 99%